Preparation of MOF-based catalyst and application of MOF-based catalyst in catalytic oxidation desulfurization
By designing FeOOH/UiO-66 catalysts, various problems existing in the oxidative desulfurization treatment of existing catalysts are solved, and high-efficiency deep desulfurization is achieved at room temperature and at normal pressure, with good reusability and economic benefits.
Patent Information
- Application Number
- CN202510078802.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-29
AI Technical Summary
In the oxidative desulfurization treatment, existing catalysts have problems such as insufficient surfactant center, harsh reaction conditions, poor selectivity, catalyst deactivation and complex reaction systems, especially lacking catalysts that can efficiently desulfurize at room temperature and at normal pressure.
A MOF-based catalyst is designed, consisting of FeOOH and metal organic framework UiO-66, prepared by hydrothermal method and grown FeOOH in situ on UiO-66 to form a FeOOH/UiO-66 catalyst.
The catalyst exhibits high-efficiency deep desulfurization at room temperature and at normal pressure, has good reusability and economic benefits, complies with the requirements of the National VI standard, and significantly improves the activity and stability of the catalyst.
Smart Images

Figure CN119897166A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to the preparation of MOF-based catalysts and their application in catalytic oxidation desulfurization. Background Art
[0002] The sulfur in the fuel will generate sulfur dioxide during the combustion process, which will be further oxidized in the atmosphere to form sulfate aerosols, which will not only cause acid rain, but also have serious impacts on the environment and human health. In addition, sulfur oxides will also cause photochemical smog and haze, affecting air quality, so oxidative desulfurization treatment is required.
[0003] However, the commonly used catalysts have the following problems when used for oxidative desulfurization: (1) Insufficient surface active centers: Many traditional metal oxide cluster anions (such as POMs) have problems such as small surface area and easy solubility in solvents when used as heterogeneous catalysts; (2) Harsh reaction conditions: Oxidative desulfurization technology usually requires high temperature and high pressure conditions, which not only increases energy consumption but also may cause damage to equipment; (3) Poor selectivity: In some cases, the selectivity of the catalyst is not high and it is impossible to effectively distinguish the target sulfide from other compounds; (4) Catalyst deactivation: During the oxidative desulfurization process, the catalyst is easily deactivated due to elemental sulfur deposition or sulfate formation; (5) Complex reaction system: When using solid catalysts for oxidative desulfurization, complex auxiliary means are usually required to ensure sufficient contact between the catalyst, oxidant and oil-soluble sulfide, which may lead to fuel emulsification and difficulty in continuous production process; (6) Insufficient development of catalyst structure and functional materials: Although research has been devoted to optimizing MOFs materials, the pore characteristics of most MOFs cannot enable aromatic sulfur-containing compounds to directly reach the inorganic metal center. Therefore, MOFs materials usually appear as carriers in catalytic oxidative desulfurization reaction systems; (7) Lack of efficient and stable catalysts: There is currently a lack of catalysts on the market that can efficiently desulfurize at room temperature and atmospheric pressure, which limits the scope of application of oxidative desulfurization technology.
[0004] Therefore, in order to address the problem that the above-mentioned catalysts cannot efficiently desulfurize at room temperature and normal pressure, the preparation of MOF-based catalysts and their application in catalytic oxidation desulfurization can be designed. Summary of the invention
[0005] In order to overcome the problems of low concentration efficiency and inability to recover heat.
[0006] The technical solution of the present invention is: a MOF-based catalyst, which is composed of FeOOH and a metal organic framework UiO-66;
[0007] The loading ratio of FeOOH and metal organic framework UiO-66 is 1:(2.5~5).
[0008] Preferably, the size of the metal organic framework UiO-66 is 110 nm.
[0009] The preparation of the MOF-based catalyst comprises the MOF-based catalyst as described above, and the steps are as follows:
[0010] Step 1: Preparation of metal organic framework UiO-66 by hydrothermal method;
[0011] Step 2: FeOOH is then in situ grown on the metal organic framework UiO-66 to obtain a MOF-based catalyst composed of FeOOH and the metal organic framework UiO-66.
[0012] Preferably, the specific steps of preparing the metal organic framework UiO-66 by hydrothermal method are:
[0013] (1) Add 0.8 mmol of zirconium chloride and 0.8 mmol of terephthalic acid to 82 mL of N,N-dimethylformamide, stir magnetically for 60 min, and then continue ultrasonication for 20 min to obtain a mixed solution 1;
[0014] (2) The mixed solution was transferred to a high-pressure reactor and placed in an oven for reaction at 120°C and normal pressure for 24 hours. After cooling to room temperature, the mixture was washed three times by centrifugation with N,N-dimethylformamide and methanol. The solid obtained by centrifugation was transferred to an oven and dried at 60°C overnight to obtain the metal organic framework UiO-66.
[0015] Preferably, the specific steps of in-situ growing FeOOH on the metal organic framework UiO-66 are:
[0016] (1) 2.7020 g of ferric chloride hexahydrate, 0.1000 g of gelatin, 0.6060 g of urea and metal organic framework UiO-66 were added to 100 mL of deionized water, and the mixture was stirred magnetically for 60 min to obtain a mixed solution II;
[0017] (2) The mixed solution II was transferred to a high-pressure reactor and placed in an oven. After reacting at 80°C and normal pressure for 21 hours, the mixture was cooled to room temperature, centrifuged at 8000 rpm / min for 5 minutes, and the precipitate was collected. The precipitate was washed three times with ethanol and then dried in a vacuum at 65°C overnight to obtain the FeOOH / UiO-66 catalyst.
[0018] The use of a MOF-based catalyst in catalytic oxidation desulfurization comprises the MOF-based catalyst as described above, which is used for oxidative removal of organic sulfur substances in liquid fuel at room temperature.
[0019] Preferably, the steps are: mixing the MOF-based catalyst and the liquid fuel, then adding an oxidant to perform an oxidative desulfurization treatment to remove organic sulfur substances in the liquid fuel.
[0020] Preferably, the liquid fuel includes one or more of gasoline, kerosene, diesel, and fuel oil. The concentration of organic sulfur substances in the liquid fuel is 100 to 500 ppm. The organic sulfur substances in the liquid fuel can be selected from benzothiophene, dibenzothiophene and 4,6-dimethyldibenzothiophene. The molar ratio of the oxidant to the organic sulfur substances in the liquid fuel is 12:20.
[0021] Preferably, the oxidant may be selected from hydrogen peroxide, sodium hypochlorite, tert-butyl hydroperoxide and isopropylbenzene hydroperoxide, and the reaction temperature of the oxidative desulfurization is 20 to 80°C.
[0022] The beneficial effects of the present invention include high-efficiency deep desulfurization at room temperature and pressure, simple synthesis, easy recycling, compliance with the requirements of the National VI Standard, and significant catalytic performance in the catalytic oxidation desulfurization process. Studies have shown that the sulfide in the fuel can be effectively removed. Through the introduction of Fe species, it can be effectively combined with the framework structure of UiO-66 to form a stable active site (Fe3+), thereby improving the activity and stability of the catalyst. The UiO-66 material has abundant defect sites and a stable framework structure, which enables the FeOOH / UiO-66 catalyst to provide a larger specific surface area and better porosity in the catalytic oxidation desulfurization reaction, thereby facilitating the high dispersion of active components and the timely removal of reaction heat, further improving sulfur selectivity, not only improving the desulfurization efficiency, but also having good reusability, reducing environmental pollution, and complying with the development trend of green chemistry. Due to its high-efficiency catalytic performance and good reusability, the FeOOH / UiO-66 catalyst can significantly reduce production costs and improve economic benefits in industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Shown is the SEM image of the FeOOH / UiO-66 composite material of the present invention;
[0024] Figure 2 Shown is the SEM image of FeOOH of the present invention;
[0025] Figure 3 Shown is the SEM image of UiO-66 of the present invention;
[0026] Figure 4 What is shown is the XRD spectrum of the FeOOH / UiO-66 composite material of the present invention;
[0027] Figure 5 Shown is the catalytic oxidation desulfurization efficiency diagram of the FeOOH / UiO-66 composite material of the present invention. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0029] The present invention provides an embodiment: a MOF-based catalyst, wherein the MOF-based catalyst is composed of FeOOH and a metal organic framework UiO-66;
[0030] The loading ratio of FeOOH and metal organic framework UiO-66 is 1:(2.5~5).
[0031] Preferably, the size of the metal organic framework UiO-66 is 110 nm.
[0032] The preparation of the MOF-based catalyst comprises the MOF-based catalyst as described above, and the steps are as follows:
[0033] Step 1: Preparation of metal organic framework UiO-66 by hydrothermal method;
[0034] Step 2: FeOOH is then in situ grown on the metal organic framework UiO-66 to obtain a MOF-based catalyst composed of FeOOH and the metal organic framework UiO-66.
[0035] Preferably, the specific steps of preparing the metal organic framework UiO-66 by hydrothermal method are:
[0036] (1) Add 0.8 mmol of zirconium chloride and 0.8 mmol of terephthalic acid to 82 mL of N,N-dimethylformamide, stir magnetically for 60 min, and then continue ultrasonication for 20 min to obtain a mixed solution 1;
[0037] (2) The mixed solution was transferred to a high-pressure reactor and placed in an oven for reaction at 120°C and normal pressure for 24 hours. After cooling to room temperature, the mixture was washed three times by centrifugation with N,N-dimethylformamide and methanol. The solid obtained by centrifugation was transferred to an oven and dried at 60°C overnight to obtain the metal organic framework UiO-66.
[0038] Preferably, the specific steps of in-situ growing FeOOH on the metal organic framework UiO-66 are:
[0039] (1) 2.7020 g of ferric chloride hexahydrate, 0.1000 g of gelatin, 0.6060 g of urea and metal organic framework UiO-66 were added to 100 mL of deionized water, and the mixture was stirred magnetically for 60 min to obtain a mixed solution II;
[0040] (2) The mixed solution II was transferred to a high-pressure reactor and placed in an oven. After reacting at 80°C and normal pressure for 21 hours, the mixture was cooled to room temperature, centrifuged at 8000 rpm / min for 5 minutes, and the precipitate was collected. The precipitate was washed three times with ethanol and then dried in a vacuum at 65°C overnight to obtain the FeOOH / UiO-66 catalyst.
[0041] The use of a MOF-based catalyst in catalytic oxidation desulfurization comprises the MOF-based catalyst as described above, which is used for oxidative removal of organic sulfur substances in liquid fuel at room temperature.
[0042] Preferably, the steps are: mixing the MOF-based catalyst and the liquid fuel, then adding an oxidant to perform an oxidative desulfurization treatment to remove organic sulfur substances in the liquid fuel.
[0043] Preferably, the liquid fuel includes one or more of gasoline, kerosene, diesel, and fuel oil. The concentration of organic sulfur substances in the liquid fuel is 100 to 500 ppm. The organic sulfur substances in the liquid fuel can be selected from benzothiophene, dibenzothiophene and 4,6-dimethyldibenzothiophene. The molar ratio of the oxidant to the organic sulfur substances in the liquid fuel is 12:20.
[0044] Preferably, the oxidant may be selected from hydrogen peroxide, sodium hypochlorite, tert-butyl hydroperoxide and isopropylbenzene hydroperoxide, and the reaction temperature of the oxidative desulfurization is 20 to 80°C.
[0045] Example 1
[0046] The preparation of the MOF-based catalyst comprises the MOF-based catalyst as described above, and the steps are as follows:
[0047] Step 1: Prepare the metal organic framework UiO-66 by hydrothermal method. The specific steps are as follows:
[0048] (1) Add 0.8 mmol of zirconium chloride and 0.8 mmol of terephthalic acid to 82 mL of N,N-dimethylformamide, stir magnetically for 60 min, and then continue ultrasonication for 20 min to obtain a mixed solution 1;
[0049] (2) The mixed solution was transferred to a high-pressure reactor and placed in an oven for reaction at 120°C and normal pressure for 24 hours. After cooling to room temperature, the mixed solution was washed three times by centrifugation with N,N-dimethylformamide and methanol. The solid obtained by centrifugation was transferred to an oven and dried at 60°C overnight to obtain a metal organic framework UiO-66.
[0050] Step 2: Then, FeOOH is in situ grown on the metal organic framework UiO-66 to obtain a MOF-based catalyst composed of FeOOH and the metal organic framework UiO-66. The specific steps are as follows:
[0051] (1) 2.7020 g of ferric chloride hexahydrate, 0.1000 g of gelatin, 0.6060 g of urea and metal organic framework UiO-66 were added to 100 mL of deionized water, and the mixture was stirred magnetically for 60 min to obtain a mixed solution II;
[0052] (2) The mixed solution II was transferred to a high-pressure reactor and placed in an oven. After reacting at 80°C and normal pressure for 21 hours, the mixture was cooled to room temperature, centrifuged at 8000 rpm / min for 5 minutes, and the precipitate was collected. The precipitate was washed three times with ethanol and then dried in a vacuum at 65°C overnight to obtain the FeOOH / UiO-66 catalyst.
[0053] Test Example 1
[0054] (1) Surface structure and morphology of FeOOH, UiO-66 and FeOOH / UiO-66
[0055] Taking FeOOH, UiO-66 and FeOOH / UiO-66 prepared in Example 1, the scanning electron microscope uses the interaction on the sample surface to generate secondary electrons, backscattered electrons and other signals, and obtains the surface morphology, composition and other information of the sample by detecting these signals. The SEM images are as follows: Figure 1 , Figure 2 and Figure 3 ;
[0056] (2) Composition and structure analysis of FeOOH, UiO-66 and FeOOH / UiO-66
[0057] X-ray diffraction equipment uses the diffraction phenomenon of X-rays in crystals to obtain the characteristics of X-ray signals after diffraction, and obtains diffraction patterns after processing, such as Figure 4 .
[0058] Test Example 2
[0059] The FeOOH / UiO-66 composite material prepared in Example 1, UiO-66 and FeOOH were mixed with liquid fuel respectively, and then an oxidant was added to carry out oxidative desulfurization treatment. The desulfurization efficiency was as follows: Figure 5 As shown, it can be seen that the FeOOH / UiO-66 composite material prepared in Example 1 of the present invention has a higher desulfurization effect.
[0060] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of those skilled in the art without departing from the spirit of the present invention.
Claims
1. MOF-based catalyst, characterized in that The MOF-based catalyst consists of FeOOH and a metal-organic framework, UiO-66; The loading ratio of FeOOH and metal organic framework UiO-66 is 1:(2.5~5).
2. The MOF-based catalyst according to claim 1, characterized in that: The size of the metal organic framework UiO-66 is 110 nm.
3. Preparation of MOF-based catalysts, characterized in that The method comprises the MOF-based catalyst according to claim 1, wherein the steps are as follows: Step 1: Preparation of metal organic framework UiO-66 by hydrothermal method; Step 2: FeOOH is then in situ grown on the metal organic framework UiO-66 to obtain a MOF-based catalyst composed of FeOOH and the metal organic framework UiO-66.
4. The preparation of the MOF-based catalyst according to claim 3, characterized in that: The specific steps of preparing the metal organic framework UiO-66 by hydrothermal method are as follows: (1) Add 0.8 mmol of zirconium chloride and 0.8 mmol of terephthalic acid to 82 mL of N,N-dimethylformamide, stir magnetically for 60 min, and then continue ultrasonication for 20 min to obtain a mixed solution 1; (2) The mixed solution was transferred to a high-pressure reactor and placed in an oven for reaction at 120°C and normal pressure for 24 hours. After cooling to room temperature, the mixture was washed three times by centrifugation with N,N-dimethylformamide and methanol. The solid obtained by centrifugation was transferred to an oven and dried at 60°C overnight to obtain the metal organic framework UiO-66.
5. The preparation of the MOF-based catalyst according to claim 3, characterized in that: The specific steps for in-situ growth of FeOOH on the metal organic framework UiO-66 are: (1) 2.7020 g of ferric chloride hexahydrate, 0.1000 g of gelatin, 0.6060 g of urea and metal organic framework UiO-66 were added to 100 mL of deionized water, and the mixture was stirred magnetically for 60 min to obtain a mixed solution II; (2) The mixed solution II was transferred to a high-pressure reactor and placed in an oven. After reacting at 80°C and normal pressure for 21 hours, the mixture was cooled to room temperature, centrifuged at 8000 rpm / min for 5 minutes, and the precipitate was collected. The precipitate was washed three times with ethanol and then dried in a vacuum at 65°C overnight to obtain the FeOOH / UiO-66 catalyst.
6. Application of MOF-based catalyst in catalytic oxidation desulfurization, characterized in that The MOF-based catalyst according to claim 1 is used for oxidative removal of organic sulfur substances in liquid fuel at room temperature.
7. Use of the MOF-based catalyst in catalytic oxidation desulfurization according to claim 6, characterized in that: The steps are: mixing the MOF-based catalyst and liquid fuel, then adding an oxidant to perform oxidative desulfurization treatment to remove organic sulfur substances in the liquid fuel.
8. The preparation of the MOF-based catalyst according to claim 7 and its application in catalytic oxidation desulfurization, characterized in that: The liquid fuel includes one or more of gasoline, kerosene, diesel and fuel oil. The concentration of organic sulfur substances in the liquid fuel is 100-500 ppm. The organic sulfur substances in the liquid fuel can be selected from benzothiophene, dibenzothiophene and 4,6-dimethyldibenzothiophene. The molar ratio of the oxidant to the organic sulfur substances in the liquid fuel is 12:
20.
9. The preparation of the MOF-based catalyst according to claim 7 and its application in catalytic oxidation desulfurization, characterized in that: The oxidant may be hydrogen peroxide, sodium hypochlorite, tert-butyl hydroperoxide and isopropylbenzene hydroperoxide. The reaction temperature of the oxidative desulfurization is 20 to 80°C.